Effects of Coenzyme Q10 in Conjunction With Vitamin E on Retinal-evoked and Cortical-evoked Responses in Patients With Open-angle Glaucoma - Vincenzo Parisi; Marco Centofanti; Stefano Gandolfi; Dario Marangoni; Luca Rossetti; Lucia Tanga; Mariagrazia Tardini; Salvatore Traina; Nicola Ungaro; Michele Vetrugno; Benedetto Falsini (2012)
To evaluate pattern-evoked retinal and cortical responses [pattern electroretinogram (PERG) and visual-evoked potential (VEP), respectively] after treatment with coenzyme Q10 in conjunction with vitamin E in open-angle glaucoma (OAG) patients.Forty-three OAG patients (mean age, 52.5±5.29 y; intraocular pressure <18 mm Hg with β-blocker monoterapy only) were enrolled. At baseline and after 6 and 12 months, simultaneous recordings of PERG and VEPs were obtained from 22 OAG patients who underwent treatment consisting of coenzyme Q10 and vitamin E (Coqun, 2 drops/d) in addition to β-blocker monoterapy (GC group), and from 21 OAG patients who were only treated with β-blockers (GP group).At baseline, intraocular pressure, PERG, and VEP parameters were similar in both GC and GP groups (analysis of variance, P>0.05). After 6 and 12 months, PERG and VEP response parameters of GP patients were unchanged when compared to baseline. In GC patients, PERG P50 and VEP P100 implicit times were decreased, whereas PERG P50-N95 and VEP N75-P100 amplitudes were increased (P<0.01) when compared to baseline. In the GC group, the differences in implicit times and amplitudes with respect to baseline were significantly larger (P<0.01) than those recorded in the GP group. The improvement (12 mo minus baseline) of VEP implicit time was significantly correlated with the changes of PERG P50-N95 amplitude (r=-0.66171, P=0.0008) and P50 implicit time (r=0.68364, P=0.00045) over a period of 12 months.Coenzyme Q10 associated with vitamin E administration in OAG shows a beneficial effect on the inner retinal function (PERG improvement) with consequent enhancement of the visual cortical responses (VEP improvement).